Decline in fertility in Paris: An intraurban spatial analysis - Brée, Sandra; Doignon, Yoann (Population space and place, 2022)
The decline in fertility has been the subject of much research, particularly on the countries that were the precursors of this historic decline. But, if research has focused on the mechanisms of the adoption of birth control, studies about the changes in fertility in cities are less frequent. To fill this gap, this article proposes to study Paris, the city where the lowest marital fertility levels were measured during the 19th century (Brée, 2017; 10.4000/lectures.22911). The objective of this paper is to understand the spread of this intensive birth control on an intraurban scale. This approach is original because there is almost no study that examines 19th century changes in fertility on an intraurban scale. We use spatial statistics and spatial panel modelling to consider both the incidence of birth control behaviour and the socio‐economic characteristics of the districts studied, and those of the neighbouring districts, to distinguish between adaptation and diffusion effects. These methods constitute another originality of the article insofar as this type of model remains very little used in historical demography. The results highlight important spatial disparities within Paris. We also show both the importance of the social composition on the level of fertility in the districts and the strong effect of the behaviours in the neighbouring districts in the fertility change.